Zagadnienia strategiczne Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie na tle innych szkół wyższych - Pietrzak, Piotr (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
Obligating put on Polish universities by the Ministry to develop strategies as well as expecting process of deepening demographic bust, compels the search for new management tools. One of the proposed solutions is Balanced Scorecard. The author of this article has compared strategies of four Polish universities: Warsaw University of Life Sciences, Poznań University of Economics, Adam Mickiewicz University in Poznań and Warmia and Mazury University in Olsztyn. He has taken into account the most important strategic issues like: mission, vision and strategic objectives.